HUBUNGAN TINGKAT STRES DENGAN TEKANAN DARAH PADA IBU RUMAH TANGGA DI KP. CILALUNG KOTA TANGERANG SELATAN - Dhiya Oelhaq Assyifa, (2023)
Background: Stress is a phenomenon that is felt by all humans. Stress is defined as feeling depressed and mental illness. Someone who is experiencing stress can cause blood pressure to increase and can cause a stroke with the result of paralysis. This condition will actually cause health problems that are often experienced by humans when entering adulthood. Objective: The purpose of this research was to determine the factors that affect stress levels, to determine the frequency distribution of stress levels in housewives aged 31-60 years. Method: This study uses Cross Sectional, and the sample in this study was a housewife with a total sample of 63 people. The parameter used to measure stress levels is DASS 42 (Depression Anxiety Stress Scales 42), while the sphygmomanometer is used to measure blood pressure. Results: The results in this study found a relationship between stress levels and blood pressure in housewives. The results showed that 28 respondents (44.4%) experienced the highest level of stress, namely the moderate level, while 44 (69.8%) experienced the highest blood pressure category. Based on the results of statistical tests that have been tested using Spearman's rho, the p-value is 0.010 or p-value <0.005.